Standardization of SARS-CoV-2 Nucleic Acid Amplification Techniques by Calibration and Quantification to the First WHO International Standard for SARS-CoV-2 RNA - Voermans, Jolanda J. C.; Mulders, Daphne G. J. C.; Beerkens, Rob J. J.; Duijn, Marlize van; Zwaan, Liesbeth van der; Rahamat-Langendoen, Janette; Eijk, Annemiek van der; Koopmans, Marion P. G.; Molenkamp, Richard (International Journal of Microbiology, 2023)
Clinical decision-making regarding isolation of SARS-CoV-2 patients is usually based on semiquantitative cycle-threshold (Ct) values without standardization. However, not all molecular assays produce Ct values, and there is ongoing discussion about whether Ct values can be safely used for decision-making. In this study, we standardized two molecular assays which use different nucleic acid amplification techniques (NAAT): the Hologic Aptima SARS-CoV-2/Flu (TMA) and Roche Cobas 6800 SARS-CoV-2 assays. We calibrated these assays against the first WHO international standard for SARS-CoV-2 RNA by using linear regression of log10 dilution series. These calibration curves were used to calculate viral loads for clinical samples. Clinical performance was assessed retrospectively using samples collected between January 2020 and November 2021, including known positives of the wild-type SARS-CoV-2 virus, the VOCs (alpha, beta, gamma, delta, and omicron) and quality control panels. Linear regression and Bland–Altman analysis showed good correlations for SARS-CoV-2 between Panther TMA and Cobas 6800 when standardized viral loads were used. These standardized quantitative results can benefit clinical decision-making and standardization of infection control guidelines.